Mild encephalitis/encephalopathy with a reversible splenial lesion due to Plasmodium falciparum malaria: a case report - Momoko Mawatari; Tetsuro Kobayashi; Shinya Yamamoto; Nozomi Takeshita; Kayoko Hayakawa; Satoshi Kutsuna; Norio Ohmagari; Tomoyuki Noguchi; Yasuyuki Kato (Tropical Medicine and Health, 2018)
Abstract Background Neurological complications from malaria cause significant morbidity and mortality. Severe cerebral malaria occurs as a result of intense sequestration of infected erythrocytes in the cerebral capillaries. However, the pathology of the reversible neurological symptoms remains unclear. We report the case of a patient with malaria who also had mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) causing transient neurological symptoms. Case presentation A 55-year-old Japanese man was admitted to our hospital with acute fever upon returning from Nigeria. Blood smears and PCR analysis revealed ring forms in the erythrocytes, indicative of Plasmodium falciparum infection. He presented with dysarthria, expressive aphasia, and truncal ataxia, all of which were suggestive of cerebellar ataxia. He had no other signs or symptoms of severe malaria. Artemether/lumefantrine was started on the first day of illness. Although the parasites were undetectable on day 3 of illness, his neurological symptoms persisted. Brain magnetic resonance imaging (MRI) demonstrated a high-signal lesion in the splenium of the corpus callosum on diffusion-weighted images along with a decreased apparent diffusion coefficient. The neurological symptoms gradually improved by day 12. Brain MRI on day 16 showed complete regression of the splenic lesion. Therefore, the patient was diagnosed with MERS due to malaria. Conclusions MERS often causes transient headaches, seizures, and/or impaired consciousness. The symptoms are compatible with the reversible symptoms of cerebral malaria.